The resilience approach in social work, a perspective for the study of disability and aging - Limón Aguirre, Cecilia Guadalupe; Duarte Cruz, José María (Interacción y Perspectiva, 2024)
Currently, there is increasing interest in the study of how families with children with disabilities cope with this experience. This research analyzes the individual, family and social resilience processes of an older adult female caregiver of a 59-year-old daughter with a disability. Through a qualitative approach, the life history and the family genogram were used to investigate the feelings, experiences and challenges experienced by this woman throughout different moments of her family life cycle. After a systematic exercise of content analysis, capacities such as flexibility, optimism, adaptation, recovery and transformation were identified in the interviewee as mechanisms to face adverse situations. It is concluded that the study of resilience provides alternative theoretical and methodological elements and useful intervention strategies in social work.